Implementation of Dikia Rabano Learning Activities as Education Activities for Adults in Jorong Bangko Solok Selatan - Muhammad Iqbal; Jalius Jalius (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2019)
This research is guided by the high interest of citizens in terms of attending dikia learning activity. This point is proven by the high extent of citizen's presence to study in every meeting. Furthermore, the residents also study a responsive toward the delivered theory by the tutor so as it generates a few questions in terms of the theory. This research intends to see the implementation of dikia learning activity as an adult activity on Jorong Bangko South Solok. An example method of this is stratified random sampling. The data collection technique utilizes a percentage formula. The result of the research shows that (1) the goal of implementation of dikia learning can be achieved effectively, (2) sources of learning on the performance of dikia learning activity have been fulfilled appropriately, (3) learning method on the implementation of dikia learning activity is conducted properly, (4) tool of learning on the implementation of dikia learning activity is suitable with theory’s dikia art, (5) assessment of learning on the implementation of dikia learning has been conducted properly.Keywords: Learning Dikia, Adult Education